CORPORATE SOCIAL RESPONSIBILITY BY FOREIGN DIRECT INVESTMENT IN BLOCK PASE UPSTREAM OIL AND GAS SECTOR, EAST ACEH REGENCY, INDONESIA - Hidayah Balqis; Nurdin MH (Universitas Syiah Kuala, 2022)
This article explains the regulation of CSR and what factors support and hinder the implementation of CSR in foreign direct investment in the upstream oil and gas sector in the Pase Block, East Aceh. The result shows that the implementation of CSR in the Pase Block was not in accordance with Law on Governing Aceh number. 11/ 2006, Qanun Aceh No. 5/2018 on investment, Qanun Aceh Timur Number 12/ 2016 on CSR, Government Regulaiton number 65/ 2016 on the guideline for CSR and ISO 26000, as well as Production Sharing Contract between parties. The company has not implemented CSR in accordance with the laws and regulations due to the lack of commitment of TPI to implement CSR. As a result, the CSR has not positively impacted the economic growth of the community and the environment around the company.